The Role Of Regional Government Regarding Registration Of Geographical Indications: a Study In Pontianak City - Dina Karlina; Devina Puspita Sari (Jurnal Ilmu Sosial Mamangan, 2024)
Geographical indication is economically beneficial for the region where the geographical indication originates and can carry the name of the region where the geographical indication originates to the global market. These benefits must be maximized by the Regional Government as a source of regional income. This article promotes several roles of regional governments regarding geographical indications normatively and theoretically as well as what obstacles regional governments face in the process of applying for rights to geographical indications, with a case study in Pontianak City. The discussion will be carried out using normative juridical methods. The results of the discussion found that the role of regional governments regarding geographical indications includes the role 1) in the identification and registration process, 2) in supporting the marketing of geographical indication products, and 3) in providing legal protection and law enforcement. The Pontianak City Government has played a role in the identification process, informing the community in the Pontianak City area by participating in socialization conducted by the West Kalimantan Regional Office of the Ministry of Law and Human Rights regarding products that can be registered as rights for geographical indication, the importance of registration and the benefits of the right to geographical indication. The obstacle faced by the Pontianak City Government is that even though the Pontianak City Government is participating in this socialization, products that have the potential to be registered as geographical indication rights do not yet exist.